SU118. Cognitive Impairment and Clozapine Response in Treatment-Resistant Schizophrenia—A Cross-Sectional Study - Nakajima, Shinichiro (Schizophr Bull, 2017)
Background: Response to clozapine is proposed to be a marker by which patients with schizophrenia can be stratified into biologically distinct subgroups. While cognitive impairment is a core symptom of schizophrenia, few studies have examined the relationship between cognitive function and response to clozapine in patients with treatment-resistant schizophrenia. Methods: This study included 16 patients with schizophrenia who responded to clozapine (age: 43.2 ± 11.9 y; female 37.5%), 19 patients who did not respond to clozapine (44.6 ± 11.3 y; 26.3%), and 19 healthy controls (HC) (44.1 ± 12.5 y; 31.6%). Participants were age and sex matched. The following cognitive assessments were administered: Executive Interview (EXIT), Finger Tapping (FT), Grooved Pegboard (GP), Letter Fluency (F, A, and S) (LF), Letter-Number Span (LNS), Mini-Mental Status Exam (MMSE), Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), Stroop Test, Trail Making Test A and B (TMT), and Wechsler Test of Adult Reading (WTAR). Cognitive functions were compared among the 3 groups using analyses of variance with a significant P-value less than 0.0022 (0.05/23). If there was a significant difference among them, post hoc Tukey’s tests were conducted with a significant P-value less than 0.0038 (0.05/13). Results: PANSS total, positive subscale, and global subscale scores were higher in nonresponders than in responders (P < .001, P < .001, and P < .001, respectively). Significant differences were found in scores of WTAR, EXIT, RBANS Immediate Memory, Visuospatial/Constructional, Language, Attention, and Delayed Memory domains, GP, LF F test, LNS, Stroop Color-Word tests, and TMT B among the 3 groups (P < .001, P ≤ .001, P < .001, P = .001, P < .001, P < .001, P < .001, P < .001, P = .001, P < .001, P < .001, P < .001, respectively). No differences were found in MMSE, FT, LF A and S tests, Stroop Color test, and TMT A scores, and score ratios of Stroop Color and Color-Word tests and TMT A and B. Among these 13 domains, there was no domain where any difference was found between responders and nonresponders. WTAR, EXIT, RBANS Language domain, LF F test, and Stroop Color-Word test scores were lower in nonresponders than HC without any significant differences among other comparisons. Both responders and nonresponders performed significantly worse than HC on RBANS Total scale, Immediate Memory, Visuospatial/Constructional, Attention, and Delayed Memory domains, GP, LNS, and TMT B without any significant differences between responders and nonresponders. Conclusion: Regardless of response to clozapine, patients with treatment-resistant schizophrenia appear to have impairments in attention, processing speed, working memory, cognitive control/executive function, and visual learning. These results are consistent with the finding that cognitive symptoms are generally unresponsive to antipsychotic treatment.